Implementation of the Simultaneous Village Head Election (PILKADES) Policy in Banjar Regency, Indonesia. - Jamaluddin, Jamaluddin; Muthahhari, Muhammad; Al Syahrin, M Najeri (Technium Social Sciences Journal, 2023)
This research aims to find out what policies or decisions were taken by the Banjar Regency Government in the process of selecting the Serentah Village Head in Banjar Regency and how they relate to preventing COVID-19. Apart from that, we also try to find out how the implementation of the policy is seen from the aspect of communication, community economic resources, or the economic condition of the community, and the Aluh-Aluh District as the policy implementer along with the Village Officials involved. This research uses a qualitative research approach. The research informants are relevant stakeholders from elements of the regional government, sub-district, and village officials as well as the community who are considered to know a lot about policy implementation. Apart from that, to understand and represent the phenomena surrounding the simultaneous village head election activities in Banjar Regency in 2022. The overall results of the research in the field stated that 9 villages held village elections simultaneously and that the implementation of the village elections peacefully and democratically went well based on information from the Community and Village Empowerment Service of Banjar Regency. This is supported by factual data in the field that there were no lawsuits or disturbances during the implementation of the Village Head Election. It’s just that a lawsuit was filed by one of the losing village head candidates, namely from the incumbent in Aluh-Aluh Besar Village regarding the DPT, but the complaint and objection were submitted outside the time determined by the committee. So the lawsuit was resolved at the village committee level. For the other 8 villages, there were no lawsuits or complaints from village head candidates because the elected Village Heads were mostly trusted by the majority of village residents. The difference that occurred with the implementation of the previous Village Head Election was the obstacle in adjusting to the COVID-19 pandemic situation that occurred. This creates a lot of adjustments and even conflicts to be faced. There is a need to strengthen democracy systematically and participatively from both regional government and village officials who are synchronized and connected to achieve an effective and efficient village head election.